Flexible germanium (Ge) nanomembranes and devices - Mak, Sin Hua (Nanyang Technological University, 2024)
Semiconductors are the fundamental of current technology and are infused into devices used daily, ranging from personal devices to healthcare and defence systems. As the demand for these devices increase continuously, compact, lightweight and portability become crucial factors in producing semiconductor device. Germanium nanomembrane (Ge NM) is one of the common materials used in semiconductor field, Ge has an indirect bandgap but can be altered significantly with application of mechanical stress such as tensile stress. The application of strain can improve the performance of Ge especially in optoelectronics. Due to its advantages optical properties, Ge NM has become the centre of interest as a viable option for flexible device in various field such as biomedical and defence systems. Hence, flexible nanomembrane devices are highly sought after with its wide applications. In this Final Year Project report, will present the documentation of the fabrication and characterisation of germanium diode using Raman spectroscopy and current-voltage measurement setup. In this study, experiments were to investigate the application effect of the uniaxial tensile strain and compressive stress on Ge NM based photodiodes. The application of the tensile strain and compressive stress are conducted through fixing the Ge NM at a bent state. The Raman peak measurement will be conducted when Ge NM is in three different states, this includes Ge Nm with no strain or stress applied, Ge NM with tensile strain applied and Ge NM with compressive stress applied. The Raman peak of Ge NM without strain or stress is observed at 300.11221 cm−1, while Ge NM with tensile strain is observed at 299.18874 cm−1 and Ge NM with compressive stress is observed at 300.67749 cm−1. The uniaxial tensile strain The significance of this research will contribute to the improvement and enhancement of the current flexible Ge NM devices. Enable Ge diodes to be implemented into more of the present devices to be developed as a higher performance portable device.